Cystic Endometriosis in a Huge Degenerated Subserous Leiomyoma Mimicking Bilateral Multicystic Endometriomas in an Infertile Woman with Diminished Ovarian Reserve: A Rare Endometriotic Implantation. (29th February 2016) - Hatirnaz, Safak; Colak, Sabri; Reis, Abdulkadir
Abstract : Uterine leiomyomas are the most common pelvic tumor in women. Leiomyoma can show atypical locations and degenerations and may not be easily differentiated from adnexal masses. Uterine leiomyoma can undergo cystic degeneration and is said to be found in 4% of all types of degenerations. The commonest type of degeneration is hyaline seen in 60% of patients. Usually uterine leiomyoma does not present as clinical and radiological diagnostic challenge. However, when leiomyoma undergoes massive cystic degeneration they may become clinical and radiological diagnostic dilemmas. The MRI showed a huge cystic mass protruding up to the pelvis not differentiated from bilateral endometriomas and accompanying subserous myomas. Surgery revealed that the mass is not bilateral endometriomas but a huge pedunculated leiomyoma with cystic degeneration and cystic endometriosis. Endometriosis is a troubling gynecologic condition occurring in 10% to 15% of women of reproductive age and is associated with fertility problems. As a peritoneal disease, the locations of endometriotic lesions are predominantly the ovaries (96.4%), followed by the soft tissue (2.8%), gastrointestinal tract (0.3%), and urinary tract (0.2%) and other rare locations. The presented case is multiple sized cystic endometriosis (endometriomas) located in a huge pedunculated subserous leiomyoma in an infertile woman having a history of laparoscopic bilateral endometrioma surgery. Conclusion . To our knowledge, this is the first reported case for endometriotic cysts (endometriomas) located in a huge cystic degenerated leiomyoma. PubMed search revealed no report concerning endometriotic implantation in the leiomyomas.